Formation of motivation to learn the vocation-related language - Vlada, Nikitina (2021)
The current situation on the global education market bears the need for new approaches to learning Russian as a foreign language. The innovation concerns both professors and students’ activity. The success in comprehension of scientific language is largely dependent on students’ motivation to study the vocation-related language. The article covers the methodological basis of the approach which may improve preparatory department students’ motivation to study.